EXPLORING WATER QUALITY AS A DETERMINANT OF THE EXISTENCE OF SOFT SHELL CRAB (SCYLLA OLIVACEA) IN DIFFERENT HABITATS OF THE LARGE MARINE ECOSYSTEM IN THE BAY OF BENGAL. - Md. Jahidul, Hasan (ZIBELINE INTERNATIONAL, 2024)
The present study determined the concentration of semicarbazide (SEM) in water and soil samples from diverse habitats of mud crabs encompassing natural breeding grounds, mangrove-associated rivers, different commercial farms and the tissue samples in soft-shell crabs. Semicarbazide is a residue of banned veterinary drug nitrofurazone that can be found in some natural crustaceans that have never been exposed to nitrofurazone. Analysis of water and soil sediment confirmed the presence of SEM in natural habitat, however the concentrations was very low as <0.1 ng/g throughout the study. The extraction and analysis of nitrofuran metabolites was conducted by using liquid chromatography-tandem mass spectrometry (LCMS/ MS) methods. The commercial farms of mud crabs were also exhibited the lowest levels of SEM in both water (0.0003 ng/g) and soil sediment (0.0005 ng/g). Tissue-specific SEM analyses encompassing muscle, shell-muscle composite, and shell revealed a distinct spatial gradient in which shell tissues exhibiting the highest concentration of SEM (3.51±0.03 ng/g) in commercial farms, surpassing those observed in muscle tissues (0.33±0.01 ng/g). Remarkably, crabs from commercial farms exhibited higher SEM concentrations across all tissue types compared to those from natural breeding grounds. However, no SEM was detected in crab feed snail and tilapia fish in commercial farms, suggesting feed composition may not be a major contributor. The lowest concentrations of SEM in water and soil sediments towards physiological processes rather than environmental contamination as the source. This study highlights limitations of SEM as a sole nitrofuran abuse marker, advocating for broader regulatory frameworks and calls for reevaluating regulations to ensure public health and responsible aquaculture.